Vibroacoustic reciprocity principle in examination of musical instruments - Engel, Z.; Gawlik, M. (Archives of Acoustics, 2002)
An application of the Reciprocity Principle for investigating certain acoustic parameters of the contrabass was presented in the paper. By means of direct measurements the vibroacoustic transfer function between the force occurring in the bridge of the contrabass and the acoustic pressure in the observation point was obtained. By means of reciprocity measurements the vibroacoustic transfer function between the volume velocity of the point sound source and the velocity of vibration of the element of the contrabass bridge was obtained. The compatibility of those transfer functions as well as the usefulness of the reciprocity method in acoustic examinations were assessed. Spectra of some sounds emitted by the contrabass were determined.